Comparative evaluation of low-level laser therapy and nanometric calcium phosphate desensitizing agent on cervical dentin hypersensitivity - A case report - De Araujo, Ariani T.S. [UNESP]; Elossais, André A.; Barros, Ana C.P. [UNESP]; Jordão-Basso, Keren C.F. [UNESP]; Manso, Rafael W.C.; Rastelli, Alessandra N.S. [UNESP]; Andrade, Marcelo F. [UNESP] (IOP Publishing, 2018)
The aim of this case report is to analyze the efficacy of different desensitizing treatments using a nanometric calcium phosphate-based product and low-level laser therapy applied in cervical dentin hypersensitivity. A patient presenting non-carious cervical lesions was selected. Split mouth study design was performed according to the following groups: Group 1 (Desensitizing Nano P®- desensitizing agent) and Group 2 (Whitening Lase II® laser). Before and after each application, probing, water-spray and air-spray stimuli were carried out. Afterwards, the patient pain score was evaluated using the visual analogic scale. Data were submitted and the Kruskal-Wallis test and Friedman's test at a 1% significance level were carried out. After 3 weeks, both treatments presented pain sensation reduction.
Keywords: dentin; dentin hypersensitivity; desensitizing agent; low-level laser therapy